Solar Panel Cleaning Robot - Dr. (Mrs.) S. P. Washimkar; Sharvari Gulhane; Ayush Vaidya; Jyotiraditya Tidke; Devanshu Kawade (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Solar energy is one of the most sustainable and widely used renewable energy sources. However, dust, dirt, and environmental pollutants accumulate on solar panels, significantly reducing their efficiency by up to 30-40%. Manual cleaning is labour-intensive, inefficient, and impractical for large-scale installations. This project presents an IoT-based Solar Panel Cleaner Robot that automates the cleaning process, ensuring maximum energy output. The system consists of a robotic cleaning mechanism, dust sensors, microcontroller-based control unit, and IoT integration. The dust sensor detects dirt accumulation, while a light sensor monitors power efficiency loss. When cleaning is required, the robotic system activates a motorized brush, air blower, or water sprayer, effectively removing dust. The entire process is controlled by an ESP32 microcontroller, which also sends real-time data to an IoT dashboard using Wi-Fi. Users can remotely monitor and control the system through a mobile app.